Interrelationships of caregiver mental health, parenting practices, and child development in rural China. (February 2021) - Zhong, Jingdong; Wang, Tianyi; He, Yang; Gao, Jingjing; Liu, Chengfang; Lai, Fang; Zhang, Liuxiu; Luo, Renfu
Highlights: Parental investment and skill mediate caregiver mental health and child development. Caregiver depression are more harmful to parenting practices and child development. The variety of play material has significant mediation effect on child development. Coercive parenting mediate caregiver mental health and child development. Abstract: Background: Parenting practices are associated with early childhood development (ECD), and some evidences suggest that mental health might affect parenting practices. However, the interrelationships of mental health, parenting practices, and ECD outcomes have not yet been well documented in developing contexts like rural China. Objective: This paper aims to investigate the interrelationships between the caregiver's mental health, parenting practices, and the child's ECD outcomes in rural China. Methods: A total of 1787 sample households in an undeveloped rural area of western China are enrolled in the study. A socioeconomic questionnaire, the Depression, Anxiety and Stress Scale, the Family Care Indicators, the Parent and Family Adjustment Scales, and the Bayley Scales of Infant Development version III were used to measure the socioeconomic characteristics of sample households, the caregiver's mental health, parental investments and parenting skills, and the child's development outcomes, respectively. Mediation model was then applied to estimate the interrelationships. Results: The results showed that parental practices significantly mediated between the caregiver's mental health and the child's cognition, language, motor, and social–emotion development. Through parental investments, one standard deviation increases in the caregiver's mental health test score was associated with the decline in the child's four development scores by 0.6% standard deviation, respectively. Through parenting skills, one standard deviation increases in the caregiver's mental health test score was associated with the decline in the child's language and social-emotional score by 2% and 5% standard deviation, respectively. Different dimensions of caregiver mental health, parental investments and skills played heterogeneous roles in the interrelationships. Conclusions: Early interventions aimed at improving the caregiver's mental health, parental investments and skills are important and might be effective to improve early childhood development in rural China.